ONO-1078 reduces NMDA-induced brain injury and vascular cell adhesion molecule-1 expression in rats - ZHANG Li-hui; WEI Er-qing (Acta Pharmacologica Sinica, 2016)
Aim: To determine whether ONO-1078 (pranlukast), a potent cysteinyl leukotriene receptor 1 (CysLT1) antagonist, has an effect on N-methyl-D-aspartate (NMDA)- induced brain injury and vascular cell adhesion molecule-1 (VCAM-1) expression in rats. Methods: Brain injury was induced by direct microinjection of NMDA (0.3 μmol in 1 μL of sterile 0.1 mol/L PBS, pH 7.4) into the cerebral cortex. The lesion volume (area), brain edema and neuron density were assessed by an image analyzer and the expression of VCAM-1 in the cortex was detected by Western blot 24 h after NMDA injection. ONO-1078 (0.03, 0.1, or 0.3 mg/kg) and edaravone (MCI-186, 10 mg/kg), a neuroprotective agent, were ip injected 30 min before and after NMDA injection. Results: NMDA microinjection produced well-defined focal lesions (Figure 1) dose- and time-dependently. ONO-1078 (0.1, 0.3 mg/kg) and edaravone (10 mg/kg) decreased the total lesion volume, lesion area and brain edema induced by NMDA. Furthermore, ONO-1078 (0.1, 0.3 mg/kg) significantly inhibited the enhanced expression of VCAM-1 in the injured cortices, but edaravone did not have this effect. Conclusion: CysLT1 receptor antagonist ONO-1078 attenuates NMDA-induced brain damage in rats, and this might relate to the attenuation of NMDA receptor-dependent neurotoxicity and the inhibition of the upregulation of VCAM-1 expression.